Distribution systems of insecticide-treated bed nets for malaria control in rural Burkina Faso: cluster-randomized controlled trial. - Olaf Müller (Public Library of Science (PLoS), 2008)
Background Insecticide-impregnated bed nets (ITNs) have been shown to be a highly effective tool against malaria in the endemic regions of sub-Saharan Africa (SSA). There are however different opinions about the role of ITN social marketing and ITN free distribution in the roll-out of ITN programmes. The objective of this study was to evaluate the effects of free ITN distribution through antenatal care services in addition to an ITN social marketing programme in an area typical for rural SSA. Methods A cluster-randomised controlled ITN trial took place in the whole Kossi Province in north-western Burkina Faso, an area highly endemic for malaria. Twelve clusters were assigned to long-term ITN (Serena brand) social marketing plus free ITN (Serena brand) distribution to all pregnant women attending governmental antenatal care services (group A), and 13 clusters to ITN social marketing only (group B). The intervention took place during the rainy season of 2006 and thereafter. The trial was evaluated through a representative household survey at baseline and after one year. Serena ITN household ownership was the primary outcome measure. Findings A total of 1052 households were visited at baseline in February 2006 and 1050 at follow-up in February 2007. Overall Serena ITN household ownership increased from 16% to 28% over the study period, with a significantly higher increase in group A (13% to 35%) than in group B (18% to 23%) (p<0.001). Interpretation The free distribution of ITNs to pregnant women through governmental antenatal care services in addition to ITN social marketing substantially improved ITN household ownership in rural Burkina Faso. Trial registration Controlled-Trials.com ISRCTN07985309.